An Update of the Hypothetical X17 Particle - Attila J. Krasznahorkay; Attila Krasznahorkay; Margit Csatlós; János Timár; Marcell Begala; Attila Krakó; István Rajta; István Vajda; Nándor J. Sas (Universe)
Recently, when examining the differential internal pair creation coefficients of 8Be, 4He and 12C nuclei, we observed peak-like anomalies in the angular correlation of the e+e− pairs. This was interpreted as the creation and immediate decay of an intermediate bosonic particle with a mass of <semantics>mXc2≈</semantics> 17 MeV, receiving the name X17 in subsequent publications. In this paper, our latest results obtained for the X17 particle are presented by investigating the e+e− pair correlations in the decay of the Giant Dipole Resonance (GDR) of 8Be. Our results initiated a significant number of new experiments all over the world to detect the X17 particle and determine its properties. In this paper, we will also conduct a mini-review of the experiments whose results are already published, as well as the ones closest to being published.